Responsabilidad penal por contaminación del aire y la vulneración del derecho constitucional de la naturaleza - Guamán Guamán, Ángel Ruperto (2014)
This thesis has the overall objective to analyze the constitutional rights that protects and guarantees the rights of nature and the Air Pollution violent states the right to live in a healthy environment. For these reasons it was thought necessary to prepare and present this research thesis that seeks to guarantee the right to outdoor pollution. To this end, the problem analysis made it possible to identify some problem areas and in turn point out the following. To develop the research work and the above, submitted the following formulation, How does air pollution in small amounts with smog violates the Constitutional principle of Nature? Clearly the violation of the rights of air by humans, especially in the private and public, since they do not say anything and act injuring the constitutional right of the air. While the literal b of Article 607A of the Environmental Violations of the Ecuadorian Criminal Code reads: "Accumulate waste in public places, on land or in front of houses or buildings, but does not indicate to burn garbage." For such situations a reform proposal was formulated paragraph b of Article 607A of the Environmental Violations of the Criminal Code to ensure the right environment in subjection to the Universal Principles of air